Protein Traffic Is an Intracellular Target in Alcohol Toxicity - Esteban-Pretel, Guillermo (MDPI, 2011)
Eukaryotic cells comprise a set of organelles, surrounded by membranes with a unique composition, which is maintained by a complex synthesis and transport system. Cells also synthesize the proteins destined for secretion. Together, these processes are known as the secretory pathway or exocytosis. In addition, many molecules can be internalized by cells through a process called endocytosis. Chronic and acute alcohol (ethanol) exposure alters the secretion of different essential products, such as hormones, neurotransmitters and others in a variety of cells, including central nervous system cells. This effect could be due to a range of mechanisms, including alcohol-induced alterations in the different steps involved in intracellular transport, such as glycosylation and vesicular transport along cytoskeleton elements. Moreover, alcohol consumption during pregnancy disrupts developmental processes in the central nervous system. No single mechanism has proved sufficient to account for these effects, and multiple factors are likely involved. One such mechanism indicates that ethanol also perturbs protein trafficking. The purpose of this review is to summarize our understanding of how ethanol exposure alters the trafficking of proteins in different cell systems, especially in central nervous system cells (neurons and astrocytes) in adult and developing brains.